An in situ poly(carboxybetaine) hydrogel for tissue engineering applications. (4th January 2017) - Chien, Hsiu-Wen; Yu, Jiashing; Li, Shing Tak; Chen, Hsin-Yu; Tsai, Wei-Bor
Abstract : Hydrogels provide three-dimensional (3D) frames with tissue-like elasticity and high water content for tissue scaffolds. Abstract : Hydrogels provide three-dimensional (3D) frames with tissue-like elasticity and high water content for tissue scaffolds. Previously, we reported the design and synthesis protocol of a biodegradable poly(carboxybetaine) poly(CB) hydrogel with a zwitterionic carboxybetaine methacrylate (CBMA) monomer and a disulfide-containing crosslinker via free radical polymerization. We also demonstrated that cells could be successfully encapsulated in the hydrogels without compromising cytoviability. In this study, we evaluated the cytoviability of three commonly used zwitterionic monomers (CBMA, 2-methacryloyloxyethyl phosphorylcholine (MPC) and sulfobetaine methacrylate (SBMA)) and the suitability of being utilized as precursor materials for in situ gel forming implants. These three zwitterionic monomers exhibited lower cell toxicity than other methacrylated monomers. Mixing these monomers with dimethacrylate crosslinkers initiated the gelation process in situ, which was further tested in vivo by injecting the precursor solutions subcutaneously into murine models. Poly(CB) implants retained their original shape up to 3 weeks, while poly(MPC) and poly(SB) hydrogels for shorter periods of time due to lower mechanical strengths. These hydrogels showed minimal inflammation at the injection site. We subsequently showed that the CBMA precursor solution mixed with Arg-Gly-Asp (RGD) and hydroxyapatite (HAp) nanoparticles could be applied in bone tissue engineering. Both in vitro and in vivo studies demonstrated that HAp containing poly(CB) hydrogels greatly enhanced the mineralization process of bone tissue formation. The non-cytotoxic and biodegradable poly(CB) hydrogel conjugated with cell affinity moieties is an excellent material for 3D tissue scaffolds.